The effect of financial ratio and firm size on firm value, with sustainability report as a moderating variable - Vira Virgiana Ningsih; Frido Saritua Simatupang (Jurnal Ekonomi, 2024)
The purpose of this study was to determine whether there is an influence of financial ratio and firm size on firm value, with sustainability report as a moderating variable. The sample of this research was 12 firm sector food and beverage listed on the IDX in 2020-2022. This research is descriptive statistics. The method used in this study is quantitative method with multiple linear regression analysis techniques and Moderated Regression Analysis (MRA). The results of research with the t test show that EPS has a significant positive effect on firm value, SIZE has a significant negative effect on firm value and SR*EPS has a significant negative effect on firm value. While CR, SR*CR, and SR*SIZE has no effect on firm value.